Community Media in a Pandemic: Facilitating Local Communication Collective Resilience and Transitions to Virtual Public Life in the U.S. - Haywood, Antoine; Aufderheide, Patricia; Sánchez, Mariana (Javnost-The Public, 2021)
This article examines how US community media organisations anchored to public, educational and government (PEG) cable channels facilitated community resilience during the 2020 pandemic. We find evidence that they served as active “meso-agents” (institutional actors) in local communication networks. Some 230 completed survey responses and 10 open-ended interviews with PEG staffers demonstrated that access media commonly performed essential functions including official and community communication and teacher training in new virtual platforms; providing news, especially coordinating official information; and providing “contactless community,” with virtual versions of ritual occasions. These creative responses also suggest new ways to address “news deserts” in the US, if chronic problems with spotty broadband, underfunding of PEG services and lack of federal incentives can be addressed.